The lichens and lichenicolous fungi of limestone outcrops of the nature reserve “Yelanetsky step” (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The list of the lichens and lichenocolous fungi of limestone outcrops of the nature reserve “YElanetsky step” includes 64 species lichens and 6 species lichenocolous fungi of 29 genera, 16 families, 6 orders and group mitosporic fungi. Toninia physaroides (Opis) Zahlbr., Stigmidium glebarum (Arnold) Hafellner, Zwackiomyces calcariae (Flagey) Hafellner & Nik. Hoffm. are firstly reported for Ukraine, Aspicilia farinosa (Flörke) Arnol, Clauzadea metzleri (Korber) D. Hawksw., Bacidina delicata (Larbal. ex Leight) V. Wirth et Vĕzda, Gonohymenia myriospora (Zahlbr.) Zahlbr., Hymenelia prevostii Koerb., Rinodina dubiana (Hepp) J. Steiner – for plain part of Ukraine, and Caloplaca polycarpa (A. Massal.) Zahlbr, Collema undulatum Laurer ex Flot., Lecanora xanthostoma CI. Roux ex Fröberg, Verrucaria macrostoma DC. – for steppe part of Ukraine. Data about ecology and frequency of occurrence of the lichens and lichenicolous fungi are provided.
Keywords: lichens fungi, lichenicolous fungi, limestone outcrops, nature reserve “YElanetsky step”.